Scalable Protection for MPEG-4 Fine Granularity Scalability - Zhu, Bin Benjamin; Yuan, Chun; Wang, Yidong; Li, Shipeng (IEEE Trans. on Multimedia, 2005)
The newly adopted MPEG-4 fine granularity scalability (FGS) video coding standard offers easy and flexible adaptation to varying network bandwidths and different application needs. Encryption for FGS should preserve such adaptation capabilities and enable intermediate stages to process encrypted data directly without decryption. In this paper, we propose two novel encryption algorithms for MPEG-4 FGS that meet these requirements. The first algorithm encrypts an FGS stream (containing both the base and the enhancement layers) into a single access layer and preserves the original fine granularity scalability and error resilience performance in an encrypted stream. The second algorithm encrypts an FGS stream into multiple quality layers divided according to either peak signal-to-noise ratio (PSNR) or bit rates, with lower quality layers being accessible and reusable by a higher quality layer of the same type, but not vice versa. Both PSNR and bit-rate layers are supported simultaneously so a layer of either type can be selected on the fly without decryption. The base layer for the second algorithm may be unencrypted to allow free view of the content at low-quality or content-based search of a video database without decryption. Both algorithms are fast, error-resilient, and have negligible compression overhead. The same approach can be applied to other scalable multimedia formats.